Fractional Order PID Controlled Cascaded Re-boost Seven Level Inverter Fed Induction Motor System with Enhanced Response - P. Bhaskara Prasad; M. Padma Lalitha; B. Sarvesh (International Journal of Power Electronics and Drive Systems (IJPEDS), 2018)
Recently, Re-boost seven-level inverter has been developed as an alternative between Photovoltaic system and single-phase load. DC level is increased using a re-boost regulator and its output is rehabilitated into single-phase AC utilizing a seven-level inverter. The re-boost converter is utilized to escalate the voltage gain. The objective of the suggested closed loop Re-boost Seven Level Inverter fed Induction Motor (RBSLIIM) system is to enhance the dynamic response of RBSLIIM using FO-P-I-D controller. Simulink models are developed for P-I and FO-P-I-D controlled RBSLIIM systems. The results of P-I and FO-P-I-D based RBSLIIM systems indicate that the voltage response with FO-P-I-D is superior to P-I controlled RBSLIIM system.